Inconstancy - Aycock, Roger D., 1914-2004; Summers, Leo, 1925-1985 (Salt Lake City, UT : Project Gutenberg, 2023)
"Inconstancy" by Roger D. Aycock is a science fiction novella written during the early 1960s. The book explores the complexities and challenges of an interplanetary romance between a Martian ambassador, Mirrh Yahn y Cona, and a Terran woman, Leila Anderson. The narrative examines themes of tradition, cultural differences, and the emotional turmoil that arises from the expectations of loyalty and love. The story follows Mirrh Yahn y Cona as he arrives on Earth, where he grapples with feelings of discomfort and longing for his Martian fiancée, Yrml. Despite his training and preparation, Earth proves chaotic and unpredictable, leaving him bewildered. As he gets to know Leila, he finds himself drawn to her, complicating his obligations to Yrml back on Mars. Through a series of encounters and a growing personal connection, the story delves into the idea of inconstancy in love, highlighting the cultural contrasts that shape their perspectives. Ultimately, the narrative culminates in a decision that challenges Mirrh's loyalty, raising questions about duty and the nature of love across planetary boundaries. (This is an automatically generated summary.)
Release date is 2023-11-22
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Man-woman relationships -- Fiction; Martians -- Fiction; Diplomacy -- Fiction